Perilaku Harga pada Pasar Tradisional dan Modern untuk Komoditas Daging Ayam Ras di Kota Jambi (Periode Sebelum, Awal dan Masa Pandemi Covid 19) - Afriani H; Muhammad Farhan; Farizal Farizal; Firmansyah Firmansyah; Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2022)
The purpose of this study was to analyze the price behavior of purebred chicken before, at the beginning and during the Covid-19 pandemic in traditional and modern markets in Jambi City. This research is a quantitative research with secondary data analysis. This study uses secondary data in the form of time series data, namely daily data on the price of purebred chicken in traditional and modern markets in Jambi City with the period: a) Before the Covid 19 Pandemic, namely the period March 2019 to February 2020 sourced from the Strategic Food Price Information Center. National; b) The beginning of the Covid 19 Pandemic, namely the period March 2020 to August 2020 sourced from the National Strategic Food Price Information Center; c) The Covid 19 Pandemic period is the period from September 2020 to September 2021. The analysis used to calculate the price behavior of purebred chicken is a descriptive analysis based on the coefficient of price variation. The growth rate of broiler meat prices at traditional markets in Jambi City is higher than the growth rate of purebred chicken meat prices at modern markets in Jambi City both before, early and during the Covid-19 pandemic. The behavior of the price of purebred chicken before, at the beginning and during the Covid-19 pandemic at traditional markets in Jambi City was unstable or fluctuated high. Meanwhile, the price behavior of purebred chicken in the period before, at the beginning and during the Covid-19 pandemic in the modern market in Jambi City was stable or fluctuated low, except for the period before the Covid-19 pandemic.